Optimization of Pulsed Nd:YAG Laser Melting of Gray Cast Iron At Different Spot Sizes for Enhanced Surface Properties - A. R., Zulhishamuddin; S. N., Aqida; E. A., Rahim (AIP Publishing LLC, 2016)
This paper presents a laser surface modification process of gray cast iron using different laser spot size with an aims to eliminate graphite phase and achieve minimum surface roughness and maximum depth of molten zone and microhardness properties. The laser processing was conducted using JK300HPS Nd:YAG twin lamp laser source pulse TEM 00 mode, 50 W average power, 1064 nm wavelength and different laser spot sizes of 1.0 mm, 1.2 mm, 1.4 mm and 1.7 mm. Three controlled parameter were peak power (Pp), pulse repetition frequency (PRF) and traverse speed (v). Increasing spot size the parameter setting where peak power is increased and pulse repetition frequency and traverse speed is decreased. The modified surface of laser surface melting was characterized for metallographic study, surface roughness and hardness. Metallographic study and surface morphology were conducted using optical microscope while hardness properties were measured using Vickers scale. Surface roughness was measured using a 2D stylus profilometer. From metallographic study, the graphite phase was totally eliminated from the molten zone and formed white zone. This phenomenon affected hardness properties of the modified surface where maximum hardness of 955.8 HV0.1 achieved. Optimization of laser surface modification was conducted for minimum surface roughness and maximum depth of modified layer and hardness properties. From the optimization, the higher desirability is 0.902. The highest depth of molten zone obtain from spot size 1.4 mm at 132 µm and the highest hardness is 989 HV0.1 at laser’s spot size 1.0 mm. The surface roughness increased when the spot size increased from 3.10 µm to 7.31 µm. These finding indicate potential application of enhanced gray cast iron in high wear resistance automotive components such as cylinder liner and break disc.